Maxillary osteonecrosis induced by antiresorptive medication (bisphosphonate) in a patient with multiple myeloma - Case report (Research, Society and Development, 2020)
Objective: to describe the clinical case of a patient with multiple myeloma, who developed maxillary osteonecrosis induced by anti-resorptive medication (bisphosphonate) submitted to a conservative and surgical therapeutic approach and subsequent prosthetic rehabilitation. Patients and methods: the case report is presented based on a simple review of the literature and clinical experience for the diagnosis, clinical staging of the lesion, carrying out the excision of the necrotic bone, debridement, lesion control and making a obturator prosthesis. Results: Despite the difficulty offered by the pathological condition and continuous use of medication, the treatment employed was successful, restoring health and providing a better quality of life to the patient, which allowed the obturation prosthesis to be made in the 8-month postoperative period. Conclusion: The result obtained emphasizes the importance of knowledge of the staging of the lesion for the application of the treatment protocol, in addition to recognizing patients at risk for the practice of prevention in dental treatments.